Postplanting Nutritional Augmentation of Jeffrey Pine Seedlings on an Infertile Sierran Site - Roger F. Walker (International Journal of Forestry Research)
Broadcast fertilization with an array of amendments was investigated for its capacity to stimulate growth and enhance nutrition of a three-year-old Jeffrey pine (Pinus jeffreyi Grev. & Balf.) plantation growing on an acidic Sierra Nevada surface mine. Four formulations that differed in N source, duration of release, and the suite of nutrients provided were evaluated, with each applied using four rates. Free Flow 29-3-4, a conventional amendment featuring urea as its near exclusive N source, and High N 22-4-6, a controlled release formulation containing ammoniacal, nitrate, and urea N, were the most stimulatory while an organic formulation relying exclusively on a municipal biosolid N source, Milorganite 6-2-0, was the least so. The lowest application rates employed were inadequate while the most advantageous was not the highest rate for any formulation. Foliar analysis revealed that improved N nutrition was probably critical in the favorable growth responses to fertilization, that of P was a likely contributor, and amelioration of potential Mn toxicity may have assumed an accessory role.